2021
DOI: 10.21608/aasj.2021.83602.1071
|View full text |Cite
|
Sign up to set email alerts
|

Land capability and suitability of some soils at North-West of Dashlut, Assiut, Egypt

Abstract: Twelve soil profiles representing North-West of Dashlut area, Assiut, Egypt were selected and dug, and 43 soil samples were collected from these profiles to evaluate its productive capability and suitability for growing selected crops. The soils of this area had a coarse texture grades (sand, loamy sand, and sandy loam). Most of these soils were highly saline (ECe > 16 dS/m) and showed low values of organic matter and available NPK, some of these soils are considered as calcareous. Tow modern programs includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Capability and suitability maps were generated using GIS tools. El- Sayed et al (2020) successfully mapped capability and suitability of soils in Sohag using GIS-Geostatistical model while Sayed and Khalafalla (2021) recommended the same procedure for mapping land evaluation results. Abosafia et al (2022) could map their outputs of land evaluation models for some parts of Kafr-Elsheikh using GIS tools.…”
Section: Gis Mapping Of Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Capability and suitability maps were generated using GIS tools. El- Sayed et al (2020) successfully mapped capability and suitability of soils in Sohag using GIS-Geostatistical model while Sayed and Khalafalla (2021) recommended the same procedure for mapping land evaluation results. Abosafia et al (2022) could map their outputs of land evaluation models for some parts of Kafr-Elsheikh using GIS tools.…”
Section: Gis Mapping Of Soilmentioning
confidence: 99%
“…Moreover, Ibrahim et al (2013) mentioned that the integration of GIS and remote sensing was found to be an effective tool for sustainable land use planning. Sayed and Khalafalla (2021) concluded that GIS technique with geostatistical tools is a valuable approach for capability and suitability evaluation of land. For land suitability evaluation, there many layers of data related to soil parameters, climatic conditions, social and environmental impacts of a specific land use that planned to be evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Lands are evaluated according to their chemical and physical capabilities as well as constraints to protect soil resources from degradation through the potential to fulfill farmers' demands for optimum crop production (Sharififar, 2012). Geographic information systems technique combined with geostatistical analysis is an effective method for assessing the capacity and suitability of land (Sayed and Khalafalla 2021). Images from remote sensing (RS) are an effective technique for studying the T Egyptian Journal of Soil Science http://ejss.journals.ekb.eg/ ____________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…Land evaluation using different models such as ASLE model (El-Seedy, 2019), ALES-Arid model (Mahmoud et al, 2020;Nada et al, 2022), and MicroLEIS model (Yousif, 2019) by integration with GIS techniques. Sayed and Khalafalla (2021) used GIS techniques for land evaluation of some soils in Northwest of Dashlut, Assiut, Egypt. The same techniques were used for the same purpose in Eastern Sohag (Moursy et al, 2020), Tushka area (Abd El-Aziz, 2018), Southwest of Aswan city (Aldabaa and Yousif, 2020), ElQusiya Area, Assiut (Fadl and Sayed, 2020), and Bahariya Oasis (Shokr et al, 2022).…”
Section: Introductionmentioning
confidence: 99%